Biochemical evaluation of X-linked hypophosphatemia and tumor-induced osteomalacia: insights into diagnosis and management - Díaz-Garzón Marco, Jorge; Aguado Acín, Pilar; Jodar Gimeno, Esteban; Fernández Calle, Pilar; Lopes Martín, Vanessa; González-Casaus, María Luisa (Frontiers in Endocrinology, 2025)
IntroductionX-linked hypophosphatemia (XLH) and tumor-induced osteomalacia (TIO) are characterized by alterations in phosphate metabolism due to elevated levels of fibroblast growth factor 23 (FGF23). These conditions cause significant morbidity due to chronic hypophosphatemia and resulting musculoskeletal disorders.ObjectiveThis study aims to provide clinical strategies for supporting the diagnosis and management of the biochemical profile of patients with XLH and TIO, addressing key considerations beyond the hypophosphatemia and hyperphosphaturia commonly observed in these conditions and addressing the variability and limitations of current biochemical marker detection methods.Materials and methodsA literature search focused on studies published in the last ten years. A multidisciplinary team analyzed the data to integrate the findings into clinical best practices.Results and discussionThe proposed approach emphasizes correctly performing and interpreting tests for serum phosphate, phosphaturia, FGF23, alkaline phosphatase (ALP), parathyroid hormone (PTH), vitamin D, serum calcium, and the calcium-corrected excretion rate. More standardization in screening methods is needed, which affects diagnostic accuracy and management. The recommendations include detailed protocols for patient preparation, sample collection, and interpretation of results.ConclusionsThe recommendations for performing biochemical screening for XLH and TIO promote better clinical practices in patient diagnosis and management. Future research should focus on validating diagnostic methods in diverse populations and standardizing biochemical tests. Multidisciplinary approach to the diagnosis of these patients through the close collaboration of professionals of laboratory medicine and clinical specialties would be pivotal.